Drug-Eluting Stent Versus Coronary Artery Bypass Grafting for Diabetic Patients With Multivessel and/or Left Main Coronary Artery Disease: A Meta-Analysis. (September 2019) - Cui, Kongyong; Lyu, Shuzheng; Song, Xiantao; Liu, Hong; Yuan, Fei; Xu, Feng; Zhang, Min; Wang, Wei; Zhang, Mingduo; Zhang, Dongfeng; Tian, Jinfan
With the development of stent design and surgical techniques, the relative benefit of percutaneous coronary intervention (PCI) versus coronary artery bypass grafting (CABG) in patients with diabetes and complex coronary artery disease are highly debated. This meta-analysis was conducted to compare the outcomes of drug-eluting stent (DES) implantation and CABG in these cohorts. A comprehensive search of PubMed, Embase, and Cochrane Library up to January 4, 2018, was performed. Only randomized controlled trials (RCTs), subgroup analysis from RCTs, or adjusted observational studies were eligible. Five RCTs and 13 adjusted observational studies involving 17 532 patients were included. Overall, PCI with DES was significantly associated with higher risk of all-cause mortality (hazard ratio [HR]: 1.16, 95% confidence interval [CI]: 1.05-1.29), myocardial infarction (MI; HR: 1.69, 95% CI: 1.43-2.00), and repeat revascularization (HR: 3.77, 95% CI: 2.76-5.16) compared with CABG. Nevertheless, the risk of stroke was significantly lower in the DES group (HR: 0.67, 95% CI: 0.54-0.83). The incidence of the composite end point of death, MI, or stroke was comparable between the 2 groups (HR: 0.99, 95% CI: 0.84-1.17). Despite the higher risk of stroke, CABG was better than PCI with DES for diabetic patients with multivessel and/or left main coronary artery disease.